2022
DOI: 10.1002/pits.22728
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and wellbeing in Romanian teachers during the COVID‐19 pandemic: The intervening effects of job crafting and problem‐focused coping

Abstract: This study examines the relationship between teacher perceived stress during the online period of schooling in the coronavirus disease 2019 pandemic, and their wellbeing, with job crafting as a mediator, The study also examines the role of problem‐focused coping as a moderator in the stress‐job crafting relationship. A sample of 360 teachers, 347 females, and 13 males, aged 21–63 years answered to an online survey from October to December 2020. Regression analyses were employed to the data. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
12
2
Order By: Relevance
“…Thus, the teachers’ responses to our questionnaire indicated that their perceived stress was proportionally higher than that recorded in teachers during the SARS epidemic in 2003. A similar study on teachers’ stress in Romania during the COVID-19 pandemic reported a mean perceived stress of 2.35 (out of 5) using the 14-item Perceived Stress Scale [ 66 ], which was lower than that measured in our study. Our findings are comparable with the key results presented in a recent systematic review [ 67 ], in which the rate of reported stress symptoms ranged from 8.1% to 81.9% in studies of the general population in China, Spain, Italy, Iran, the United States, Turkey, Nepal, and Denmark during the first 6 months of the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Thus, the teachers’ responses to our questionnaire indicated that their perceived stress was proportionally higher than that recorded in teachers during the SARS epidemic in 2003. A similar study on teachers’ stress in Romania during the COVID-19 pandemic reported a mean perceived stress of 2.35 (out of 5) using the 14-item Perceived Stress Scale [ 66 ], which was lower than that measured in our study. Our findings are comparable with the key results presented in a recent systematic review [ 67 ], in which the rate of reported stress symptoms ranged from 8.1% to 81.9% in studies of the general population in China, Spain, Italy, Iran, the United States, Turkey, Nepal, and Denmark during the first 6 months of the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 86%
“…Self-endangering work behaviours can be viewed as a coping mechanism when workers are challenged with large workloads and significant needs for self-organisation [ 37 ]. During the pandemic, increased workloads, work demands and working hours have been reported by teachers and educators around the world [ 19 , 66 ]. Teachers have been required to immediately transition to remote teaching, which became a major stressor in their work [ 19 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies give insight into mechanisms explaining teachers’ well-being in forced remote work. The effect of teachers’ stress on well-being is mediated by job crafting for people that score low on problem-focused coping [ 8 ]. On the other hand, Gao et al [ 9 ] confirmed the problem-focused coping strategy as a direct mechanism for maintaining good health and reducing the risk of developing PTSD in the face of stress.…”
Section: Introductionmentioning
confidence: 99%
“…They were multi-tasking (Gold et al, 2009), workload (Gold et al, 2009Simbula et al, 2012;Vazi et al, 2013;Vesely et al, 2013;Bermejo-Toro et al, 2015;Desrumaux et al, 2015;Yerdelen et al, 2016;Helms-Lorenz & Maulana, 2016;Skaalvik & Skaalvik, 2017;Alvarado & Bretones, 2018;Alloh et al, 2019;Braun et al, 2019;Soykan et al, 2019;Brady & Wilson, 2020;Carroll et al, 2020;Farley & Chamberlain, 2021;Hepburn et al, 2021a;Ibrahim et al, 2021;Tebben et al, 2021;Billett et al, 2022), lack of professional recognition and appreciation, administration overload, role conflict, poor working condition, time pressure, lack of recourses and technology, appeared as organisational factors which contributed to teachers' stress. Workload was the prominent category which was recorded in most of the studies to be the key factor for emotional exhaustion among teachers (Bower & Carroll, 2017) and burn out (Chang, 2009). Often inseparably connected with workload was due to increasing work demands from leadership team, extensive student performance and short deadlines.…”
Section: Organisational Stress Factorsmentioning
confidence: 99%